Of constitutional commissions and expert-led interpretation during processes of constitutional change - VISSER, De Maartje (Institutional Knowledge at Singapore Management University, 2020)
In an 1816 letter, Thomas Jefferson expressed himself in favour of including a provision in the constitution that would prescribe its regular upkeep. “[E]ach generation”, the Founding Father wrote, ought to be able to revise the constitu- tion “every nineteen or twenty years”, so it could “be handed on, with periodical repairs, from generation to generation, to the end of time.” As we know, his advice was not heeded: the U.S. Constitution is notoriously difficult to change, with the longest interval between two amendments running to slightly more than six decades. Closer to home, the Singapore Constitution similarly does not mandate generational maintenance. The absence of any prescription to that effect, however, has not inhibited regular revision, occasionally at a pace that even exceeds the Jeffersonian idea. The amendment that forms the central focus of this volume sought to reform the Presidency about a generational interlude – 25 years to be exact – after it became a popularly elective office. When first announcing the prospect of changes to the institution of the Elected President, Prime Minister Lee Hsien Loong noted, in language evocative of that used in the 1816 letter, that “we need to continue to review and adjust the scheme regularly, to keep it functional and in good repair”